PROFESOR JÓZEFAT ZIELONACKI (1818-1884) NA TLE XIX -WIECZNEJ PANDEKTYSTYKI - Zięba, Agnieszka (Zeszyty Prawnicze, 2017)
Prof. Jozefat Zielonacki (1818-1884) against the Background of the XIXth Century Study of Pandects Summary The study of pandects is the study of the intercepted Rom an law formed and developed in the XIXth century Germany. The pandectist made use of the Justynian codification and their research m ethod was shaped under the influence of so called historical school in jurisprudence created by F.K. Savigny. Conducting a research on unparalleled scale on the Rom an law and with a time rejecting the historical perspective therein led to a creation o f an abstract scientific system - the „contemporary Rom an law”, viz. the study of pandects. In the second half of the XIXth century it dom inated the European study of law. The Polish representative of this branch was Jozefat Zielonacki, a graduate o f the Berlin University, a pupil of F.K. Savigny. H e lectured the Roman law at universities in Cracow (from which it was repealed after two years as a result of anti-Plish victimisation), Innsbruck, Prague, and Lwow. He stayed in Lwow from 1857 to 1870, contributing to ‘Polonisation’ of the university and establishing a well-founded centre of the Roman law study, well-admitted in Europe of that time. As far as the research method is concerned, Prof. Zielonacki constantly remained a pandectist - he created ahistorical works and the Roman law is treated therein as the prototype o f the contemporary binding law. The study of pandects is nowadays treated as one of numerous great periods of the history of the study of law and its achievements: the ordination, m ethod of thinking and terms retain their usefulness also for the contemporary study of civil law.